Sanctions and Foreign Direct Investment: Damage to Russia and Sanctioning Countries - S. V. Kazantsev (Мир новой экономики)
The volume and dynamics of foreign investments are formed under the influence of many conditions and circumstances. The author of this article examines the impact of one class of factors that determine the dynamics and geographical structure of Russia’s foreign direct investment inflows outflows. These are anti-Russian sanctions imposed by a group of States in 2014 to isolate the Russian Federation in the field of politics, finance and economy, science and technology, information and culture. For these countries, Russia is not a priority investment target. The share of the Russian Federation varied from two to five per cent, and rarely exceeded 10 per cent of the total volume of these countries foreign direct investment net outflows in 2007–2018. The author presented in this article the positive and negative aspects of foreign direct investment, their dynamics before and after the imposition of sanctions. In particular, the author shows that the reduction in the foreign direct investment net inflows from Russia to the sanctioning countries was less significant for the leading EU States — Germany, France and United Kingdom — than for many other sanctioning countries The cuts in Russia’s foreign direct investment net outflows had almost no impact on the United States who was the main initiator of anti-Russian sanctions.